Output stream of a leaky integrate-and-fire neuron - Vidybida, A.K. (Reports of the National Academy of Sciences of Ukraine, 2014)
The probability density function of output interspike intervals is found in the exact form for a leaky integrate-and-fire neuron stimulated with a Poisson stream. The diffusion approximation is not exploited.